Empirical evidence on structural racism as a driver of racial inequities in COVID-19 mortality - Brown, Tyson H.; Kamis, Christina; Homan, Patricia (Frontiers in Public Health, 2022)
Objective This study contributes to the literature by empirically testing the extent to which place-based structural racism is a driver of state-level racial inequalities in COVID-19 mortality using theoretically-informed, innovative approaches. Methods CDC data are used to measure cumulative COVID-19 death rates between January 2020 and August 2022. The outcome measure is a state-level Black-White (B/W) ratio of age-adjusted death rates. We use state-level 2019 administrative data on previously validated indicators of structural racism spanning educational, economic, political, criminal-legal and housing to identify a novel, multi-sectoral latent measure of structural racism (CFI = 0.982, TLI = 0.968, and RMSEA = 0.044). We map B/W inequalities in COVID-19 mortality as well as the latent measure of structural racism in order to understand their geographic distribution across U.S. states. Finally, we use regression analyses to estimate the extent to which structural racism contributes to Black-White inequalities in COVID-19 mortality, net of potential confounders. Results Results reveal substantial state-level variation in the B/W ratio of COVID-19 death rates and structural racism. Notably, regression estimates indicate that the relationship between the structural racism and B/W inequality in COVID-19 mortality is positive and statistically significant (p < 0.001), both in the bivariate model (adjusted R2 = 0.37) and net of the covariates (adjusted R2 = 0.54). For example, whereas states with a structural racism value 2 standard deviation below the mean have a B/W ratio of approximately 1.12, states with a structural racism value 2 standard deviation above the mean have a ratio of just above 2.0. Discussion Findings suggest that efficacious health equity solutions will require bold policies that dismantle structural racism across numerous societal domains.